Studies of Calcium Absorption in Man Using a CD-2 Whole-Body Counter - Bakos, K.; Wernischová, Věra (Nuklearmedizin - NuclearMedicine, 1977)
Whole-body counting makes an important contribution of radioisotope techniques to ȁEin vivo“ absorption studies, in comparison with other methods. In a large number of subjects, the method was tested for its usefulness in the diagnosis of calcium malabsorption. The effects of drugs, of the calcium load in the gut and of the whole-body content of calcium on the absorption process were studied in a control group.